2016
DOI: 10.1038/gt.2016.54
|View full text |Cite
|
Sign up to set email alerts
|

Single residue AAV capsid mutation improves transduction of photoreceptors in the Abca4−/− mouse and bipolar cells in the rd1 mouse and human retina ex vivo

Abstract: Gene therapy using adeno-associated viral vectors (AAV) for the treatment of retinal degenerations has shown safety and efficacy in clinical trials. However, very high levels of vector expression may be necessary for the treatment of conditions such as Stargardt disease where a dual vector approach is potentially needed, or in optogenetic strategies for end-stage degeneration in order to achieve maximal light sensitivity. In this study, we assessed two vectors with single capsid mutations, rAAV2/2(Y444F) and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 37 publications
2
27
0
Order By: Relevance
“…We have previously shown that AAV2 has the capability of transducing human retinal explants cultured ex vivo 28, 39. Here, we report that the WPRE also improves GFP expression following transduction in retinectomized human retinal tissue, in spite of its inherent atrophic nature.…”
Section: Discussionmentioning
confidence: 63%
“…We have previously shown that AAV2 has the capability of transducing human retinal explants cultured ex vivo 28, 39. Here, we report that the WPRE also improves GFP expression following transduction in retinectomized human retinal tissue, in spite of its inherent atrophic nature.…”
Section: Discussionmentioning
confidence: 63%
“…The in vivo results consistently show greater photoreceptor transduction efficiency by serotypes AAV2/5, 2/8 and 2/9, compared with the archetypal AAV2/2 vector. Recently, screening for tropism and infectivity of human retinal cells has also been performed in ex vivo human retinal explants, although the results appear to be highly variable between individual explants [15][16][17] .…”
Section: Introductionmentioning
confidence: 99%
“…In view of these constraints, we instead turned to an ex vivo organotypic culture system that allows for the tropism of the hybrid vector rAAV2/2[MAX] to be determined on human retina directly. In contrast with previous studies where fresh peripheral retina was obtained during a retinectomy, 33 , 34 we cultured central retina acquired post mortem from donor eyes. While obtaining viable postmortem retinal samples proved to be challenging, the opportunity to evaluate the transduction profile of rAAV2/2[MAX] in samples containing the macula was deemed to be of substantial clinical relevance.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, tyrosine-to-phenylalanine point mutations have also been incorporated in rAAV2/8 and rAAV2/9 vectors, improving the transduction in a wide range of tissues, including the retina, kidney, and pancreas. 33 , 35 39 Although the 7m8 peptide was chosen due to its previously demonstrated impact on rAAV-mediated photoreceptor transduction, other cell-penetrating or cell-specific targeting peptides, such as the epidermal growth factor receptor tyrosine kinase inhibitor or human immunodeficiency virus Tat peptide, 40 could be incorporated in place of the 7m8 peptide in order to improve transduction of nonretinal cell types. The insertion of some peptides can have deleterious effects on the capsid stability 41 and therefore cannot be incorporated into the capsid.…”
Section: Discussionmentioning
confidence: 99%